Boss life : surviving my own small business - Downs, Paul. (2015)
"When columnist Paul Downs was approached by The New York Times to write for their "You're the Boss" blog, he had been running his custom furniture business for twenty-four years strong. or mostly strong. Now, in his first book, Downs paints an honest portrait of a real business, with a real boss, a real set of employees, and the real challenges they face. Fresh out of college in 1986, Downs opened his first business, a small company that builds custom furniture. In 1987, he hired his first employee. That's when things got complicated. As his enterprise began to grow, he had to learn about management, cash flow, taxes, and so much more. But despite any obstacles, Downs always remained keenly aware that every small business, no matter the product it makes or the service it provides, starts with people. He writes with tremendous insight about hiring employees, providing motivation to get the best out of them, and the difficult decisions he's made to let some of them go. Downs also looks outward, to his dealings with vendors and to providing each client with exemplary customer service from first sales pitch to final delivery. With honesty and conviction, he tells the true story behind building and sustaining a successful company in an ever-evolving economy, often airing his own failures and shortcomings to reveal the difficulties that arise from being a boss and a businessperson. Countless employees have told the story of their experience with managers--Boss Life tells the other side of that story"--
Keywords: Cabinetmakers -- United States; New business enterprises -- United States -- Management; Small business -- United States -- Management; BIOGRAPHY & AUTOBIOGRAPHY / General; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Small Business; Print books